Influence of SiO2 nanoparticles on relative fluorescence of plant cells (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nanoparticles (nano-scale particles (NSPs)) are defined as particles with dimensions less than 100 nm. SiO2 nanoparticles are one of the most widely common nanoparticles in the environment, particularly in urban areas. The sources of SiO2 nanoparticles are very different, including natural nanoparticles, anthropogenic and engineered nanoparticles. The SiO2 nanoparticles could be considered a source of different pollution effects on leaving organisms. Nevertheless, knowledge of the mechanisms, through which the SiO2 nanoparticles affect cells, is incomplete. The aim of the research was to elaborate a method to determine changes in relative fluorescence of both somatic and immature gametic plant cells in presence of SiO2 nanoparticles. Relative cell fluorescence was measured with BD FACSJazz® cell sorter using 488 nm exciting laser light. Mean cell fluorescence was determined for samples of purified cell suspension. Gates of different size and shape were preliminary tested to find those with the lowest CV. Cell plots were created by BS FACS Software 1.0.0.650. The densest part of the plot was gated using oval-shaped gate. The gate included 95-99% of all cells. A logarithmic scale in arbitrary fluorescence units was applied to determine cell relative fluorescence. More than 10 000 cells were gated and analysed from each sample. Somatic cell culture from callus culture initiated from leaves of flax (Linum usitatissimum) was obtained. The relative fluorescence of the somatic cells had large distribution, since the cells differ by many parameters (size, shape, metabolism etc.). Immature pollen cells (one-nucleus stage) as best for SiO2 nanoparticles influence investigation were found. The influence of SiO2 nanoparticles on several plant species (Cyclamen persicum, Tilia cordata, Hordeum vulgare and Triticum aestivum) immature pollen cells were investigated. A significant increase in relative cell fluorescence was observed for all mentioned plant species cells after incubation in SiO2 nanoparticles suspension. It was found that cell relative fluorescence was dependent on cultivation duration in SiO2 nanoparticles suspension.